Does tertiarization explain differences in labour market behaviour?: A cross national approach refering to European Union - Carlos Iglesias-Fernández; Raquel Llorente-Heras; Juan R. Cuadrado-Roura (European Regional Science Association (ERSA), 2002)
There are ever more works which identify the service sector as the principal protagonist in the creation of employment in western economies, with respect to the recent past and in the near future. At the same time, agreement exists regarding the profound transformations that work characteristics are undergoing, a processs which can be finally expressed as an increment in what we could call "work flexibility". With reference to the previous questions, in the European Union very varied disparities can be found. Whilst employment in Ireland and in Spain increased noticeably between 1994 and 2000, (37 and 23% respectively), in Austria the increase was only 0.9% and in Germany 3%. On the other hand, we can also find great differences in labour behviour in terms of flexibility and rigidity. The thesis which we endeavour to prove in the work is double: In what measure do the services ( and their internal composition) explain both the processes of employment creation and the increment of job flexibility observed in the EU? In what measure do the differences in tertiarization (and their internal composition) in the EU countries explain the heterogeneity observed in both employment creation and increased job dynamics? For this, and by means of the data of the "European Household Panel", the paper will have the following scheme: a) In first place, the behaviour of job markets in the European Union countries will be revised (employment creation, the presence of services and the processes of tertiarization). b) Then the internal composition of the tertiary sector will be analyzed in each of these countries, checking the extent in which they are similar or different. c) Finally, using shift-share techniques the relation between tertiarization, processes of employment creation and work flexibility (through indicators of labour mobility) will be analyzed, in relation to the EU and to each of the member countries.
Keywords: 330